Utilization of Usability Repository for Final Year Students in Writing Thesis - Andien Fransiska; Herlina; Yanto (Indonesian Journal Publisher, 2025)
Abstract. This study discusses the usability of repositories for final year students in writing their theses at the Technical Implementation Unit of the Sriwijaya University Library. The purpose of this study is to determine the usability of repository applications for final year students in writing their theses at Sriwijaya University. This study used a quantitative research method with a questionnaire data collection technique that measured the level of repository utilization and usability perceptions based on the aspects of ease of use, efficiency, satisfaction, and ease of learning. Total sampling was used in this study, where the entire population of 9,319 students from the 2021 batch participated as 418 respondents. This was done to obtain a comprehensive picture of the usability of the repository based on Nielsen's theory using five categories, namely: Learnability (3.88), Efficiency (4.10), Memorability (3.87), Errors (3.04), and Satisfaction (4.21). From the results of this study, it can be concluded that Sriwijaya University students of the 2021 cohort have high usability skills. This is reflected in the high scores obtained in the five stages. Keywords: Repository; Usability; Utilization; Thesis; Sriwijaya University Library.